Investigation Of Electrical Capacitance Tomography For Agarwood Detection - Muhamad Aiqil, Sarudin (2022)
Agarwood (Aquilaria Malaccensis) or known as Gaharu in Malaysia, has high value in the market and its oil is widely used for producing medication. To get matured and quality agarwood, it needs to wait for the tree to grow and human experience cannot predict the placement and quantity of agarwood in a tree. The project aims to investigate the possibility of non-invasive method using electrical capacitance tomography for monitoring the quantity of agarwood in a tree. Based on the current research, the commonly applied tomography on method is based on sonic, magnetic inductive and microwave tomography approaches. But it is still unknown whether the voltage variations level are slight or significant in the region with resin. This work presents the development process for modeling an ECT (Electrical Capacitance Tomography) sensor using COMSOL Multiphysics. COMSOL Multiphysics software is implemented as a main tool to model the ECT system. The 8 electrodes are modeled in 2-dimensional, and it is based on the non-invasive approach. The ECT system is developed to obtain the electrical potential distribution between electrodes when an electric field is applied and to evaluate the performance analysis of proposed ECT model considering different locations, shapes, and sizes of agarwood in a tree. Moreover, the sensitivity distribution using 64x64 pixels in forward problem was solved using COMSOL and export into the MATLAB software. Then, the tomogram images of agarwood were obtained using linear back projection algorithm (LBP) in the MATLAB software. Later, the MSSIM was used as the image analysis. In short, for agarwood different size (MSSIM value = 0.1052), agarwood different position (top right) (MSSIM value = 0.1587) and agarwood phantom F (MSSIM value = 0.1081) were the reconstructed image that closely matches with the reference image because the MSSIM value ranges is between 0 to 1, whereby the value 1 means the perfect match of the reconstructed image with the original one.